2018
DOI: 10.1371/journal.pone.0199335
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel, dominant dwarfing gene (Ddw4) and its effect on morphological traits of rye

Abstract: Shortening rye stems to improve lodging resistance is among the major tasks awaiting breeders of this cereal. The most straightforward way to achieve this goal is the implementation of a dominant dwarfing gene into high yielding cultivars. The choice of dominant dwarfing genes in rye is limited to Ddw1 and Ddw3 loci, which are well characterized with respect to map position and tightly linked molecular markers on the long arms of chromosomes 5RL and 1RL, respectively. This paper reports on the identification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Despite of the promising prospects it needs to be considered that a comprehensive integration of Ddw1 in hybrid breeding programs might narrow the genetic base of rye varieties. In order to counterbalance any potential linkage drag effect, which might be driven by strong selection for a single haplotype variant controlling PH, further GA-sensitive dwarfing genes like Ddw2 (Melz, 1989), Ddw3 (Stojałowski et al, 2015), or Ddw4 (Kantarek et al, 2018) should be evaluated in breeding programs as well. The sequence information on rye GA2ox genes might support the integration of these valuable alleles in elite rye germplasm using precision breeding approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of the promising prospects it needs to be considered that a comprehensive integration of Ddw1 in hybrid breeding programs might narrow the genetic base of rye varieties. In order to counterbalance any potential linkage drag effect, which might be driven by strong selection for a single haplotype variant controlling PH, further GA-sensitive dwarfing genes like Ddw2 (Melz, 1989), Ddw3 (Stojałowski et al, 2015), or Ddw4 (Kantarek et al, 2018) should be evaluated in breeding programs as well. The sequence information on rye GA2ox genes might support the integration of these valuable alleles in elite rye germplasm using precision breeding approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Short coleoptile and low early seedling vigor associated with some dwarf genes, particularly these GA-insensitive genes, such as wheat Rht-B1b , Rht-B1c , and Rht-D1b , are the likely reasons for the lower yields in an adverse environment (e.g., deep sowing) ( Allan, 1989 ; Rebetzke et al, 1999 ; Addisu et al, 2009 ). Other studies showed some dwarfing genes negatively affected the grain yield by decreasing the grain size ( Chen et al, 2013 ), kernel thousand weight ( Kantarek et al, 2018 ), or other yield components ( Kowalski et al, 2016 ). However, the yield penalty caused by Dw6 has been assumed to be the failure of the panicle to fully emerge from the leaf sheath ( Milach and Federizzi, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of rye, dwarfing genes that efficiently decrease height without losses of yield are unknown. Until now, only four dominant dwarfing genes have been identified in rye: Ddw1 [3], Ddw2 [4], and recently, Ddw 3 [5] and Ddw 4 [6]. Attempts at introducing dwarfing genes to cultivars were carried in only the case of Ddw1 [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…There is much information about the dominant dwarfing genes of rye Ddw1 [8], Ddw3 [5] and Ddw4 [6], but little is known about recessive ones. Several recessive dwarfing genes have been identified in rye.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation